Femtosecond laser dressing of the surfaces of porous alumina grinding wheels. (24th October 2008) - Jackson, Mark J.; Robinson, Grant M.
The interaction of 180 fs, 775 nm laser pulses with the surfaces of alumina and glass under controlled gas atmospheres at ambient pressure has been investigated to study material redeposition, residual surface roughness and ablation rate. The effect of using various gases to protect the surface of the material appears to interfere with the effects of the plasma and can change the resulting microstructure of the dressed surface. By varying the combinations of fluence and laser scanning speed during ultra fast ablation at high repetition rates an optimum dressing condition can be reached. The process can be used to continuously dress porous vitrified cutting tools that are used for micro and nanogrinding processes.